Research progress on the role of type I vesicular glutamate transporter (VGLUT1) in nervous system diseases - Xianchao Du; Jiashuo Li; Minghui Li; Xinxin Yang; Zhipeng Qi; Bin Xu; Wei Liu; Zhao‐Fa Xu; Yu Deng (2020)
Abstract Glutamate (Glu) is the predominant excitatory neurotransmitter in the central nervous system (CNS). Glutamatergic transmission is critical for controlling neuronal activity. In presynaptic neurons, Glu is stored in synaptic vesicles and released by stimulation. The homeostasis of glutamatergic system is maintained by a set of transporters in the membrane of synaptic vesicles. The family of vesicular Glu transporters in mammals is comprised of three highly homologous proteins: VGLUT1-3. Among them, VGLUT1 accounts for the largest proportion. However, most of the Glu is transported into the synaptic vesicles via the type 1 vesicle Glu transporter (VGLUT1). So, the expression of particular VGLUT1 is largely complementary with limited overlap and so far it is most specific markers for neurons that use Glu as neurotransmitter. Controlling the activity of VGLUT1 could potentially modulate the efficiency of excitatory neuro-transmission and change the filling level of synaptic vesicles. This review summarizes the recent knowledge concerning molecular and functional characteristic of VGLUT1, their development, contribution to a series of central nervous system and peripheral nervous system diseases such as learning and memory disorders, Alzheimer’s disease, Parkinson’s disease and sensitized nociception or pain pathology et al.